2001
DOI: 10.1067/mhn.2001.115909
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Irrigation for the Alleviation of Sinonasal Symptoms

Abstract: Daily nasal irrigation using either a bulb syringe, nasal irrigation pot, and daily reflexology massage were equally efficacious and resulted in improvement in the symptoms of chronic sinusitis in over 70% of subjects. Medication usage was decreased in approximately one third of participants regardless of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 11 publications
1
121
0
5
Order By: Relevance
“…690,691 This review identified 12 studies evaluating saline irrigation for the management of CRS (10 RCTs, 1 systematic review, and 1 meta-analysis). 206,209,[692][693][694][695][696][697][698][699][700][701] (Table VII-13). Five RCTs evaluated saline irrigation in patients who had not undergone surgery.…”
Section: Viie1 Crs Management: Saline Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…690,691 This review identified 12 studies evaluating saline irrigation for the management of CRS (10 RCTs, 1 systematic review, and 1 meta-analysis). 206,209,[692][693][694][695][696][697][698][699][700][701] (Table VII-13). Five RCTs evaluated saline irrigation in patients who had not undergone surgery.…”
Section: Viie1 Crs Management: Saline Irrigationmentioning
confidence: 99%
“…However, there was no difference in the general QoL outcomes using the SF-12 questionnaire. The randomized trial by Heatley et al 697 compared isotonic saline irrigations, using both bulb syringe and pot irrigations, to reflexology as a control. The results demonstrated that all groups received CRS-specific QoL improvements, and surprisingly there were no difference between the reflexology and saline irrigation groups.…”
Section: Viie1 Crs Management: Saline Irrigationmentioning
confidence: 99%
“…Un aspecto promisorio e importante de su uso es la buena tolerancia descrita en la literatura, ya sea con soluciones salinas isotónicas, como con soluciones hipertónicas. Heatley y col 24 , informaron sobre la opinión de los pacientes que utilizaron soluciones salinas, donde el 70% consideraban ventajoso su uso y las recomendarían a otros pacientes. Para la mayoría de los pacientes evaluados en los diversos estudios, el efecto beneficioso de las soluciones salinas parece superar sus inconvenientes, sin embargo, la evidencia al respecto es limitada por lo que no es posible por el momento recomendar la irrigación con solución salina como parte estándar del tratamiento en rinosinusitis.…”
Section: Discussionunclassified
“…Nasal douching is a safe, inexpensive treatment commonly used in mainland Europe. Evidence exists that saline douching reduces symptoms of CRS [48][49][50][51][52][53] (grade of recommendation = A). It is a safe and inexpensive treatment.…”
Section: Treatmentmentioning
confidence: 99%